Influence of geometry, elasticity properties and boundary conditions on the Mode I purity in sandwich composites - Burlayenko, V. N.; Pietras, D.; Sadowski, Tomasz (My University, 2020)
The present work addresses the problem of skin/core debonding in sandwich materials. The main goal is to carry out parametric analyses for studying the influence of various materials, geometrical parameters and boundary conditions of sandwich fracture specimens such as a Single Cantilever Beam and a Double Cantilever Beam on the skin/core opening (KI ) and shearing (KII ) modes. The analyses have been performed by means of fracture mechanics tools implemented into the commercial finite element code ABAQUS™. A two-dimensional model of the fracture specimens has been developed with plane strain finite elements. The dependence of the stress intensity factors in the sandwich specimens on the skin thickness, ratio between the Young’s moduli of the skin and core materials and boundary conditions imposed on the specimens has been examined under quasi-static loading by using the interaction integral method.
Keywords: sandwich fracture specimens; skin/core interface debonding; bi-material system; fracture parameters; interaction integral method; finite element analysis